In the living forest an exploration of Australia's forest community : industry, science, technology, government, tourism, management, conservation, planning - Abbott, Ian (ETN Communications, 2015)
Explores the importance and contribution of forests and forestry to Australian society. Some of the foremost experts on forestry, science and the environment explore our forests' past, present and future and examine scientific innovations, economics and investment, architecture, history, education, social change and tourism
Keywords: Australien; Forests and forestry / Australia; Forests and forestry; Australia